Kupffer Cells Protect Liver Sinusoidal Endothelial Cells from Fas-Dependent Apoptosis in Sepsis by Down-Regulating gp130 - Hutchins, Noelle A. (American Society for Investigative Pathology, 2013)
Endothelial cell (EC) dysfunction is a key feature of multiple organ injury, the primary cause of fatality seen in critically ill patients. Although the development of EC dysfunction in the heart and lung is well studied in sepsis, it remains unclear in the liver. Herein, we report that liver sinusoidal ECs (LSECs; defined as CD146(+)CD45(−)) exhibit increased intercellular adhesion molecule-1 (CD54) and Fas in response to sepsis induced by cecal ligation and puncture (CLP). By using magnetically enriched LSEC (CD146(+)) populations, we show evidence of marked apoptosis, with a twofold decline in viable LSECs in CLP animals compared with sham controls. These changes and increased serum alanine aminotransferase levels were all mitigated in septic Fas(−/−) and Fas ligand(−/−) animals. Although we previously reported increased numbers of Fas ligand expressing CD8(+) T lymphocytes in the septic liver, CD8(+) T-cell deficiency did not reverse the onset of LSEC apoptosis/damage. However, Kupffer cell depletion with clodronate liposomes resulted in greater apoptosis and Fas expression after CLP and a decrease in glycoprotein 130 expression on LSECs, suggesting that STAT3 activation may protect these cells from injury. Our results document a critical role for death receptor–mediated LSEC injury and show the first evidence that Kupffer cells are essential to the viability of LSECs, which appears to be mediated through glycoprotein 130 expression in sepsis.